IMPACT OF REPLACING GRAPE POLYPHENOL WITH VITAMIN E ON GROWTH PERFORMANCE, RELATIVE ORGANS WEIGHT AND ANTIOXIDANT STATUS OF BROILERS - Z. Iqbal; R. Ali; J. I. Sultan; A. Ali; Z. Kamran; S. A. Khan; U. Ahsan (Journal of Animal and Plant Sciences, 2014)
Impact of replacing vitamin E with Grape Polyphenol (GPP) on growth performance, relative organs weight and antioxidant status of broilers was examined in the present study. A total of 280 Hubbard broiler chicks were randomly divided into 28 experimental units of 10 chicks each. A basal starter diet (control) was formulated having 22.5% CP, 3200 kcal/kg ME and 100-ppm vitamin E. The other dietary treatments were obtained by fortifying the basal diet with 25 (low GPP; LGPP), 50 (medium GPP; MGPP) and 75 ppm (high GPP; HGPP) GPP in place of vitamin E. Likewise, a finisher basal diet (20% CP and 3200 kcal/kg ME) and other dietary treatments were formulated having same proportions of GPP and vitamin E as in starter diets. Each dietary treatment was randomly assigned to seven replicate pens. Feed intake, weight gain and feed conversion ratio remained unaltered among different treatment groups during all growth periods. However, free radical scavenging activity in breast and leg muscles increased quadratically (P<0.05) with MGPP showing the highest antioxidant status (P<0.05). The organs like kidney and heart showed linear depression in weight by increasing GPP concentration while relatively lower weight of liver was observed in MGPP diet. In conclusion, replacing vitamin E with GPP in broiler diets did not exhibit difference in performance however, better antioxidant status was observed by addition of 50 mg/kg of GPP in the diet.
Keywords: grape polyphenol; antioxidant status; immune response; organs histopathology; broiler